ENHANCING HIGHER-ORDER THINKING SKILLS AND STUDENT DISCIPLINE THROUGH THE IMPLEMENTATION OF PROBLEM BASED LEARNING IN IPAS LEARNING - Riyan Supriadi; Muhammad Sofwan; Bunga Ayu Wulandari (Universitas Islam Negeri Mataram, 2025)
This study was motivated by the low level of Higher-Order Thinking Skills (HOTS) and weak learning discipline among fifth-grade students at an elementary school in Muaro Jambi during IPAS lessons. Initial observations and pretest results showed that students’ higher-order thinking abilities were still limited, with an average score of 54.76 and 0% of students meeting the minimum mastery criteria. Learning discipline was also low, indicated by only 4% of students being categorized as good. These conditions encouraged the implementation of the Problem Based Learning (PBL) model to improve cognitive performance and discipline. This research employed Classroom Action Research conducted in two cycles, each consisting of planning, action, observation, and reflection. Data were collected using HOTS tests, observation sheets, and discipline rating scales. The findings revealed a significant improvement: the average HOTS score increased to 66.24 in Cycle I and 82.92 in Cycle II, with learning mastery reaching 92%, and a normalized gain of 0.613. Student discipline also improved, with 96% categorized as good in Cycle II. These results indicate that PBL is effective in enhancing HOTS and learning discipline in IPAS learning.